PENGARUH KOMPETENSI PROFESIONAL DAN MOTIVASI EKSTERNAL TERHADAP KINERJA GURU SMK DI KOTA BANDUNG - Imam Heryanto; Windi Matsuko Danasasmita (Jurnal Computech & Bisnis (e-Journal), 2019)
The study aims to determine the effect of professional competence and external motivation on the performance of vocational school teachers in Bandung. This study used instruments sourced from Permendiknas No. 16 of 2007 for variables of professional competence and teacher performance, while instruments for external motivation variables adapted from Fernet et al. (2008). The three instruments were distributed to 100 respondents for further testing the validity and reliability of the instrument to know the question items that met the instrument's validity and reliability requirements. The next process is to test data normality. After obtaining a valid and reliable instrument, as well as data that has been normally distributed, the following process is to perform a regression analysis for the variables of professional competence and external motivation variables on the performance variables of vocational teachers. The results of multiple linear regression analysis showed the influence of professional competence and external motivation simultaneously on teacher performance by 39.9%.Keywords: professional competence, external motivation, teacher performance.